2010
DOI: 10.1007/s10695-010-9416-5
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of cadmium exposure induce DNA damage and oxidative stress in the liver of Oujiang colored common carp Cyprinus carpio var. color

Abstract: Cadmium (Cd) compounds are widely distributed toxic environmental and industrial pollutants, and they may bring danger to growth and development of aquatic organisms. In China, the Oujiang color common carp, Cyprinus carpio var. color, is a very important fish, from an economic point of view, and is well used for fish culture in paddy fields. The purpose of this study was to show the low concentrations of cadmium-induced oxidative stress response and DNA damage in the livers of Cyprinus carpio var. color. Supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…MDA is an oxidative by-product of hydroxyl radical (OH À ) converted from H 2 O 2 attack on the membrane lipids. Its content could directly reflect the degree of lipids peroxidation (Jia et al 2011). The negative association between SOD activity and MDA found in the present study had also been reported in previous studies (Tocher et al 2002;Hu et al 2011;Jia et al 2011).…”
Section: Gcsupporting
confidence: 91%
See 2 more Smart Citations
“…MDA is an oxidative by-product of hydroxyl radical (OH À ) converted from H 2 O 2 attack on the membrane lipids. Its content could directly reflect the degree of lipids peroxidation (Jia et al 2011). The negative association between SOD activity and MDA found in the present study had also been reported in previous studies (Tocher et al 2002;Hu et al 2011;Jia et al 2011).…”
Section: Gcsupporting
confidence: 91%
“…Its content could directly reflect the degree of lipids peroxidation (Jia et al . ). The negative association between SOD activity and MDA found in the present study had also been reported in previous studies (Tocher et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Both increases and decreases in GSH have been observed, depending on field and experimental conditions (Kovarova et al, 2009;Cao et al, 2010;Jia et al, 2011).…”
Section: Cadmiummentioning
confidence: 99%
“…SOD is an important antioxidant enzyme to inhibit oxyradical formation and is usually used as a biomarker to indicate oxidative stres. Superoxide dismutase, a cytosolic enzyme that is specific for scavenging superoxide radicals, is involved in protective mechanisms within tissue injury following oxidative process and phagocytosis (JIA et al 2010, LOPEZ-TORRES et al 1993. The higher the SOD value is, the more superoxide radicals need to be reacted.…”
mentioning
confidence: 99%